Historical Trace of The Spice Road as an Economic Center Indonesian Trade and Cultural Heritage - Aisyah Astinadia Siregar (Universitas Trunodjoyo Madura, 2024)
This research aims to explore the history of the Indonesian spice route as part of Indonesia's maritime cultural heritage and Indonesia's role in the spice trade route. The method used in this research is a descriptive qualitative approach with literature studies, utilizing various sources from books, journals and articles as well as ethnography and oral interviews. The results of the research show that the trade network connecting the eastern and western hemispheres of the world is known as the spice route and its impact. towards the development of local cultural identity of Indonesian society. The spice route not only refers to the trade and shipping route for spice products, but also as a cultural heritage whose traces can still be found, such as in culinary, art, medicine, clothing, traditions and even art. At that time, merchandise such as cinnamon, pepper, cloves, nutmeg, sandalwood, rice, cotton and others were traded. This route is a symbol that connects the maritime civilization of the archipelago which is Indonesia's national pride so that it can provide a new contribution to understanding the complexity of the interaction between economic factors and cultural heritage in shaping the historical landscape of the archipelago.